STUDI KASUS PUTUSAN NO. 1650/PDT.G/2017/PA.MKS TENTANG GUGATAN NASABAH YANG MERASA DIRUGIKAN OLEH PROSEDUR LELANG JAMINAN - Cahyani, Putri Tri; Mukhlas, Oyo Sunaryo (Jurnal Perspektif Hukum, 2024)
This study examines legal issues related to the execution of collateral auctions in the case of Decision No. 1650/Pdt.G/2017/PA.Mks, where a customer sued the bank, alleging harm caused by the determination of the auction’s reserve price, which was deemed too low and lacked transparency. The main issue addressed is how the court assessed the lawsuit and to what extent the auction procedures complied with the applicable legal provisions. The purpose of this study is to analyze the reasons behind the customer’s perception of harm due to the auction procedures and how the court adjudicated the dispute. The research employs a normative legal method with a literature study approach. The data sources include court decisions, journal articles, legal textbooks, and relevant regulations, such as the Law on Mortgage Rights and the Ministry of Finance Regulations on auction implementation. The findings indicate that the customer's lawsuit was declared inadmissible (Niet Ontvankelijk Verklaard) due to the court's lack of absolute jurisdiction over the dispute. Additionally, the bank's execution of the auction was found to be in compliance with the applicable legal provisions. This study underscores the importance of customers understanding legal procedures and arbitration clauses in Islamic contracts, as well as the need for greater transparency in the execution of auctions by Islamic financial institutions.